Modern Views About Genital Endometriosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Genital endometriosis is one of the most common diseases in women. Epidemiological studies indicate. that in 90-99% of patients, endometriotic lesions are detected between the ages of 20 and 50 years, most often during the reproductive period. The review is devoted to modern ideas about genital endometriosis.